The legacy of Paulo Freire. Redimensions in times of crisis. - Llanos Zuloaga, Martha (2022)
This publication is a tribute to the legacy of Paulo Freire, Brazilian educator and a world reference in the field of Education, with proposals for the development of critical thinking, inclusion, with methodologies such as action-reflection-action, the value of questions and essential dialogue for the development of autonomy, democracy and citizenship. Freire is mainly known for adult education, we met him in Peru for his contribution to literacy campaign in the Peruvian Educational Reform, later we shared in Nicaragua where I was requested by Unicef ​​to develop the CEPNES Non-Formal Children's Education Centers. This year is the 91nd anniversary of the first kindergarten in Peru and 50th anniversary of the officialization of Early Childhood Education in Peru. I present Paulo Freire's vision for early childhood education, prioritizing understanding and listening to the voices of children. Especially in this world crisis due to the COVID 19 Pandemic, I prioritize the proposals of Community and Popular Education based on the contribution of Paulo Freire and the implications in the interactions with the community and the perspectives of teacher training. The topics mentioned above are currently of urgent reflection, the crisis of the educational system, the realities of the national context imply the search for answers to the great question: what is education? What role does it play, what vision guides teaching and learning process? What is the use of current education system? How much we know our population context. Key word: Paulo Freire. Community Education, Popular Education, Autonomy, Critical thinking, self-awareness, interculturality. Children and youth education.